Animal-derived natural products of Sowa Rigpa medicine: Their pharmacopoeial description, current utilization and zoological identification. (31st July 2017) - Yeshi, Karma; Morisco, Paolo; Wangchuk, Phurpa
Abstract: Ethnopharmacological relevance: The Bhutanese Sowa Rigpa medicine (BSM) uses animal parts in the preparation of numerous polyingredient traditional remedies. Our study reports the taxonomical identification of medicinal animals and the description of traditional uses in English medical terminologies. Aim of the study: To taxonomically identify the medicinal animals and their derived natural products used as a zootherapeutic agents in BSM. Materials and methods: First, the traditional textbooks were reviewed to generate a list of animal products described as ingredients. Second, animal parts that are currently used in Bhutan were identified. Third, the ethnopharmacological uses of each animal ingredients were translated into English medical terminologies by consulting Traditional Physicians, clinical assistants, pharmacognosists, and pharmacists in Bhutan. Fourth, the animal parts were taxonomically identified and their Latin names were confirmed by crosschecking them with online animal databases and relevant scientific literature. Results: The study found 73 natural products belonging to 29 categories derived from 45 medicinal animals (36 vertebrates and 9 invertebrates), comprising of 9 taxonomic categories and 30 zoological families. Out of 116 formulations currently produced, 87 of them contain one or more extracts and products obtained from 13 medicinal animals to treat more than 124 traditionally classified illnesses. Only five animal ingredients were found available in Bhutan and rest of the animal parts are being imported from India. Conclusions: Out of 73 natural products described in the traditional textbooks, only 13 of them (some omitted and few substituted by plants) are currently included in 87 formulations of BSM. Graphical abstract: